P5 1 A New Solution To Climate Change (i) - Sanjeevvijay, Shaswathan; Munt, Leon; Iordanidis, George (Physics Special Topics, 2024)
This paper explores negating the impact of global warming due to greenhouse gases by altering the course of the Earth’s orbit. The proposal includes moving an increased distance away from the sun each year, spanning to an increase of 5 × 109 m over the course of the 95 year period 2005 - 2100.